9. A tailor has 23 metres of cloth. She wants to make 7 baju kurung of the same size. She then has 2 metres of cloth left. How many metres of cloth did she use to make each baju kurung?​

Answers

Answer 1
Answer:

Answer:

The tailor used 3m per baju kurung.

Step-by-step explanation:

The tailor began with 23m of cloth and at the end had 2m of cloth left.  You calculate how many meters of cloth she used all together by subtracting 2 from 23:

    23m - 2m = 21m

Then you find out how many meters she used per baju kurung by dividing 21 by 7:

    21m / 7m = 3m


Related Questions

Alex determines that there are 5 chocolate candies per cubic inch. If there are 150 chocolate candies in a jar, what is the volume of the jar?
What is true about the domain and range of the function?The graph of the function f(x) = (x +2)(x + 6) is shownbelow.у6The domain is all real numbers, and the range is allreal numbers greater than or equal to 4.O The domain is all real numbers greater than or equal to4, and the range is all real numbers.O The domain is all real numbers such that -65x3-2,and the range is all real numbers greater than or equalto-4.The domain is all real numbers greater than or equal to4, and the range is all real numbers such that -63x3-2.4N-6 -4 +246хN-2--46t
If M(x, y) is the midpoint of AB with A(3, 5) and B(-4, 8), then which Quadrant is M located in? (Points : 1) Quadrant I Quadrant II Quadrant III Quadrant IV Question 2. 2. Given A(9, 11), B(3, -4), C(6, -9), and D(-7, 7), then the midpoint of which line located in Quadrant II? (Points : 1) AB BC AC BD Question 3. 3. Given A(6, -17), B(-6, 17), C(4, 9), D(-4, 4), the midpoint of which segment is at the origin? (Points : 1) AB BC AC AD
3/14 of 10/9 = 5/21 is this right??
Solve x2 + 12x = –11 by completing the square. Which is the solution set of the equation?

What is the product of (x + 3)(2x – 1)

Answers

Answer:

The product of  (x + 3)(2x -1)=2x^2+5x-3

Step-by-step explanation:

Given : Two expressions (x + 3) and (2x – 1)

We have to find the product  of given expression that is  (x + 3)(2x -1)

Consider the given expression (x + 3)(2x -1)

Multiply each term of first bracket with each term of second bracket

\left(a+b\right)\left(c+d\right)=ac+ad+bc+bd

we have,

=x\cdot \:2x+x\left(-1\right)+3\cdot \:2x+3\left(-1\right)

Simplify, -(-a)=+a

we have =2xx-1\cdot \:x+3\cdot \:2x-3\cdot \:1

Simplify, we get,

=2x^2-x+6x-3

Adding like terms, we have,

=2x^2+5x-3

Thus, the product of  (x + 3)(2x -1)=2x^2+5x-3

Umm
(X+3)(2x-1)
=2x square -x + 6x - 3
=2x square +5x -3

On a blueprint of a house, 48 millimeters represents 7 meters. The length of the living room is 60 millimeters on the blueprint. what is the actual length

Answers

Here is the equation 48/7=60/x, 48÷7=6.8571428571. Now we know that every one meter in real life is equal to 6.8571428571 millimeters so, 60÷6.8571428571= 8.75 meters. The living room is 8.75 meters

Is 290.45 higher than 2867.5

Answers

2867.5 is bigger

Even though they both show 5 numbers, the second one has only one decimal place versus 2 on the first

If you ignore the decimal, your left with
290 vs 2867

2867 is much bigger than 290 so this is the answer

What percent of 66 is 133

Answers

Answer: 201.515151515% or simplified 201.5%

Hope this helped!

Please mark Brainliest!

To attend the concert, it costs $25 for parking plus $45 per ticket. If Nick paid $250, how many tickets did he purchase?

Answers

Answer:

5

Step-by-step explanation:

250-25=225

so then that means...

225 divided by 45=5

5

Which quadratic function has a leading coefficient of 2 and a constant term of –3? f(x) = 2x3 – 3 f(x) = –3x2 – 3x 2 f(x) = –3x3 2 f(x) = 2x2 3x – 3

Answers

The standard form of quadratic function is:
f(x) = a x² + b x + c
where: a - a leading coefficient,  c- constant term:
a = 2,  c = -3
Answer: D) f( x ) = 2 x² + 3 x - 3

Answer:

tHE ANSWER IS d

Step-by-step explanation: